SO2 Concentration and the Occurrence of Acute Respiratory Infection in Children Under Five - Lestari, Puji Amrih; Haryanto, Budi (Kesmas, 2022)
Jakarta is the capital city of Indonesia, with 10.7 million inhabitants with poor air quality as of 2020. Higher levels of pollution often come with an increase in the number of health risks and pneumonia cases. This study aimed to determine the association between SO2 concentration and the occurrence of acute respiratory infection (ARI) in children under five. An ecological time series design was implemented during the study by utilizing secondary data of SO2 concentrations and ARI from the Indonesian Agency for Meteorological, Climatological, and Geophysics, the Special Capital Region of Jakarta Environmental, and Health Office. Statistical correlation tests were performed to analyze the association between SO2 concentration and ARI prevalence in five municipalities cities in Jakarta from 2018-2021 based on the rainy and dry seasons. The average concentration of SO2 was 18.06–20.89 μg/m3. The SO2 concentration and the occurrence of ARI in children under five in Jakarta from 2018 to 2021 showed a weak relationship (r = 0.24). It seems that children under five in Jakarta spent their time indoors rather than outdoors; therefore, they were exposed to fewer transportation emissions.